2020
DOI: 10.4038/tare.v23i3-4.5498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic and inorganic liquid fertilizers on growth and yield of <em>Centella asiatica</em> (L.) and <em>Capsicum annuum</em> (L.) VAR. <em>annuum</em>

Abstract: Value chain management is immensely important to the management of a network of interconnected businesses involved in the eventual provision of the highest quality product and service packages required by end customers. Dairy and dairy products are highly attached by microorganisms and products are damaged due to inappropriate methods of packing, storage and transportation. Insufficient information flow; low productivity, low GDP contribution from the dairy sector; poor processing capacity and lack of chilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…At 2 nd and 3 rd picking, the maximum value of fresh pod weight was observed in T2 while minimum value in T7 at 2 nd picking and T3 at 3 rd picking. These results are agreed with Ekanayake et al (2020) stated that Fish tonic treated plants produced the highest number of pods and the fresh weight while plants treated with compost tea produced the least number of pods and the fresh weight.…”
Section: Fresh Weights Of Podssupporting
confidence: 91%
See 1 more Smart Citation
“…At 2 nd and 3 rd picking, the maximum value of fresh pod weight was observed in T2 while minimum value in T7 at 2 nd picking and T3 at 3 rd picking. These results are agreed with Ekanayake et al (2020) stated that Fish tonic treated plants produced the highest number of pods and the fresh weight while plants treated with compost tea produced the least number of pods and the fresh weight.…”
Section: Fresh Weights Of Podssupporting
confidence: 91%
“…Where nutrient uptake and good translocation rates cause the relative growth rate to be good for the whole plant as well as for other plant parts. Ekanayake et al (2020) showed that the highest stem girth was recorded in Albert's solution applied plants at flowering. However, it was not significantly different from the stem girth recorded in fish tonic treated plants.…”
Section: Girth Of Podsmentioning
confidence: 99%
“…According to the findings, the organic liquid formulation jeevamrutha is successful in helping plants in optimum growth and progress under NaCl-induced stress (Singh and Lal, 2019). Similar research has shown that using jeevamrutha in conjunction with other organic fertilizers has a good impact on the chlorophyll content of treated plants (Ekanayake, 2020). A study was done to analyze the quality and biochemical features of strawberries as influenced by organic manures; the plants treated with jeevamrutha had the maximum chlorophyll content (Sahana, 2020).…”
Section: Chlorophyll Contentmentioning
confidence: 96%